Does hope mediate the relationship between parent’s resolution of their child’s autism diagnosis and parental stress - Naicker, Vrinda V.; Hedley, Darren; Bury, Simon M. (Frontiers in Psychology, 2024)
Resolution of a child's diagnosis, the process of accepting and adjusting to the reality of a child's significant diagnosis, has been often associated with decreased parental stress. However, factors that might explain this relationship have not been as explored. Hope, a potential buffer against psychological distress, has been suggested as a potential explanation for this relationship. However, the mediating role of hope in the relationship between resolution of diagnosis and parental stress has not been explored. This study aimed to examine whether four types of hope (child, parental, societal, denial of diagnosis) mediated the relationship between resolution to an autism diagnosis and reduced parental stress. Participants included 73 parents (Mage = 43.22, SD = 7.69, Female 97.3%) of autistic children (Mage = 11.15, SD = 4.56, Male = 67.1%). Resolution to diagnosis was negatively and significantly correlated with resolution to diagnosis, as well as child, parental and societal hope. These three hopes were also significantly and negatively correlated with parental stress. Importantly, when controlling for level of support and autism awareness, parental hope mediated the relationship between resolution to diagnosis and parental stress. Denial of diagnosis was not correlated with resolution or parental stress but did have significant but weak associate with the other hopes. These findings suggest that hope based on parent's abilities to support their child and be supported themselves play an important role in parental stress once parents are more resolved to their child's diagnosis. Supporting parents to manage factors associated with supporting their child's needs, may benefit parents of autistic children.